Effective ways of struggles applied by teenage female judoka during Spanish Judo Cadets Championship - Deval, V. C.; Garcia, J.; Monteiro Luis, F.; Lopez Diaz de Durana, A. (Archives of Budo, 2010)
Background and Study Aim: To analyse the most efficient technical actions used by national-level female judokas of the cadets category (15 and 16 years), in each of the weight categories, advantages and sanctions obtained throughout the development of combats and distribution of the results achieved in each of the four-minute rounds. The objective is to establish the judokas` technical profile according to weight categories. Material/Methods: The sample consists of 116 female judokas between the age of 15 and 16, divided into seven weight categories, who participated in a total of 166 combats during the Spanish Championships. The acquisition of data was carried out by the referees selected for the study follow-up throughout the development of competition, who filled in the official entry form of each of the combats. A descriptive analysis was performed on the statistical software SPSS 14. Results: The results show that the most frequently used techniques by female judokas, the dynamic structure of the combat and the number of sanctions is similar to the ones used by high-level judokas. However in this age category the most frequent technical groups are generally the te-waza group with seoi-nage as the most efficient technique, and the sutemi-waza with tani- otoshi as the most representative technique, followed by sanctions. Conclusions: Spanish female judokas, irrespective of the weight category, achieve the higher effectiveness of the fight in the vertical posture (tachi-waza) than in the horizontal posture (ne-waza).